2023
DOI: 10.7717/peerj.16491
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Pinna nobilis population genetic structure in the Aegean and Ionian Sea

Georgia Sarafidou,
Dimitris Tsaparis,
Yiannis Issaris
et al.

Abstract: The fan mussel Pinna nobilis Linnaeus, 1758 is an endemic species of the Mediterranean Sea, protected by international agreements. It is one of the largest bivalves in the world, playing an important role in the benthic communities; yet it has been recently characterized as Critically Endangered by the IUCN, due to mass mortality events. In this context, the assessment of the genetic variation of the remaining P. nobilis populations and the evaluation of connectivity among them are crucial elements for the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Furthermore, authors set the genetic boundary between the western and eastern Mediterranean basins in the Ionian Sea, thus suggesting that, for P. nobilis, the Sicilian straits do not represent a boundary for larval dispersal. These results were then corroborated by Sarafidou et al [51], who analysed the residual genetic variation in the surviving populations after the MME from sites in the Aegean and Ionian Seas. Furthermore, based on the COI analyses, and consistent with what was previously hypothesised by Sanna et al [14], Wesselman et al [58] suggested that P. nobilis is characterised by a single mitochondrial haplogroup that experienced a recent population expansion starting from a small, original population.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Furthermore, authors set the genetic boundary between the western and eastern Mediterranean basins in the Ionian Sea, thus suggesting that, for P. nobilis, the Sicilian straits do not represent a boundary for larval dispersal. These results were then corroborated by Sarafidou et al [51], who analysed the residual genetic variation in the surviving populations after the MME from sites in the Aegean and Ionian Seas. Furthermore, based on the COI analyses, and consistent with what was previously hypothesised by Sanna et al [14], Wesselman et al [58] suggested that P. nobilis is characterised by a single mitochondrial haplogroup that experienced a recent population expansion starting from a small, original population.…”
Section: Introductionsupporting
confidence: 61%
“…Consequently, we reconstructed, with the utmost accuracy, the pre-MME phylogeographic patterns of P. nobilis in the Mediterranean Sea, shedding light on the origin of the genetic structuring between the western and eastern P. nobilis populations hypothesised in Sanna et al [14] and recently corroborated by Sarafidou et al [51] based on the analysis of Aegean and Ionian populations surviving after the MME. By utilising samples from populations not yet affected by the mass mortality of P. nobilis, we were able to study the evolutionary patterns of the species without the bias of the evolutionary forces that affected the genetic landscape of the populations due to the MME.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations